Novel Colloidal Microstructures of β-Escin and the Liposomal Components Cholesterol and DPPC - de Groot, Carolin; Müsken, Mathias; Müller-Goymann, Christel C. (Planta Medica, 2018)
The discovery of immunostimulating complex formation by the saponin Quil A from the plant Quillaja saponaria with cholesterol and a phospholipid opened up new avenues for the development of drug delivery systems for vaccine application with additional adjuvant properties. In this study, β-escin, a monodesmosidic triterpene saponin from horse chestnut, was investigated in terms of its interaction with liposomal components (cholesterol, dipalmitoylphosphatidylcholine) by Langmuir film balance studies and with regard to particle formation visualized by transmission electron microscopy. A strong interaction of β-escin with cholesterol was observed by Langmuir isotherms due to the intercalation of the saponin into the monolayer, whereas no interaction occurred with dipalmitoylphosphatidylcholine. Transmission electron microscopy studies also confirmed the strong interaction of β-escin with cholesterol. In aqueous pseudo-ternary systems (β-escin, dipalmitoylphosphatidylcholine, cholesterol) and in pseudo-binary systems (β-escin, cholesterol), new colloidal structures built up from ring-like and worm-like subunits were observed with a size of about 100 – 200 nm. These colloidal structures are formed in pseudo-binary systems by aggregation of the subunits, whereas in pseudo-ternary systems, they are formed among others by attacking the liposomal membrane. The rehydration of the liposomal dispersions in NANOpure water or Tris buffer pH 7.4 (140 mM) resulted in the same particle formation. In contrast, the sequence of the dispersionsʼ production process affected the particle formation. Unless adding the saponin to the other components from the beginning, just a liposomal dispersion was formed without any colloidal aggregates of the subunits mentioned above.
Keywords: β-escin; Aesculus hippocastanum; Sapindaceae; horse chestnut; cholesterol; phospholipid; colloidal structure; langmuir film balance; TEM